73rd Foundation Day of ICAR-CIFRI and Matsya Samridhhi Mela - Das, A K; Som, S; Das, B K (Journal of the Inland Fisheries Society of India, 2020)
ICAR-Central Inland Fisheries Research Institute (CIFRI) situated in the bank of river Ganga, at Barrackpore, West Bengal is one of the premier fishery research institutesin India. ICAR-CIFRI, since its inception has generated very useful inland fishery technologies on induced breeding and fish seed production; Composite fish culture; Fish seed prospecting and spawn collection in rivers; Reservoir and floodplain wetland fisheries management and In situ fish seed production in cage and pen. The Institute has also developed relevant guidelines for sustainable management of inland fisheries management. Dr. V. G. Jhingran, the then Director created history in the Annals of Fishery Sciences by receiving Padma Shri Award on the Republic Day of 1977 for his outstanding contribution in the field of inland fisheries. The P & T Department, Government of India, released a special postage stamp of 5 paise denomination on 26th November, 1979 in the fitness of things and as a token of recognition of the pioneering work of CIFRI in the field of aquaculture.